THE COMPARISON OF STRUCTURE BEHAVIOR ON THE HILLSIDE ZONE USING MODAL RESPONSE SPECTRUM ANALYSIS AND LINEAR RESPONSE HISTORY ANALYSIS - Kristanto Raharjo, Yohanes
Earthquake-resistant structures are necessary efforts to reduce casualties from earthquakes. As the population increases, construction in hillside areas is becoming more common. Buildings in hillside areas are more vulnerable due to their short columns and increased moment magnification caused by irregularities. Therefore, it is necessary to evaluate the structure's response to earthquakes in hillside areas. The objective of this study is to compare the response of a 10-story structure measuring 42×42 meters on slopes of 0°, 10°, 20°, and 30°. The compared structural responses include base shear force, floor displacement, and internal forces in column elements. The structural model will be analyzed using response spectrum analysis and linear time history analysis, employing three sets of ground motions. The reinforcement of the structure will meet the requirements of the Special Moment Resisting Frame System. The study results indicate that the base shear force of the structure on sloping ground increases compared to the structure on flat ground, while the floor displacement decreases as the slope angle of the ground increases due to the higher position of the columns on the ground floor. The internal forces in the ground column in the structure on sloping ground experience an increase in bending moment and shear force. The increase in internal forces in the ground column becomes more significant as the elevation of these columns increases, resulting from moment magnification due to torsional irregularities.